Mechanism of Lithium-Ion Separation Using Mixed Matrix Membrane - Waqas, Syed Ahmad (International Journal of Scientific Research and Management (IJSRM), 2024)
: The efficient recovery and separation of lithium ions are crucial for the sustainability of lithium-ion batteries (LIBs), which are pivotal in modern energy storage technologies. Mixed matrix membrane separation technology offers a promising solution for this challenge. This article delves into the mechanisms underlying Mixed Matrix membranes, their operational principles, performance metrics, and practical applications. Through a detailed examination, including graphical representations, we aim to provide a comprehensive understanding of how Mixed Matrix membranes facilitate the selective separation of lithium ions